Piezoelectric energy harvesting from DC-DC converters. Issue 1 (3rd April 2020) - Raghavendran, S.; Umapathy, M.; Uma, G.; Karlmarx, L.R.
Abstract: Energy harvesting from piezoelectric is proved to be a viable technology to source low power electronic devices. In this paper, piezoelectric energy harvester is designed such that the energy is harvested by utilizing the switching of the MOSFET in DC-DC converter, which becomes an integral part of modern industrial equipment. Energy harvesting is realized by piezoelectric and converse effect of piezoelectric material. The harvester is designed to have transmitter and receiver piezoelectric separated by metal plate, connected across the drain and source terminals of the MOSFET. The performance of the harvester is experimentally evaluated with boost converter for supercapacitor storage.